Resin composition

JP2025024777APending Publication Date: 2025-02-21SHIN ETSU CHEMICAL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023129031
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0008】 本発明の樹脂組成物は、低比誘電率、低誘電正接であり、低粗化銅との高い接着性(高いピール強度)、高い耐薬品性(高いデスミア処理耐性)、高い耐久性を有する樹脂組成物である。したがって、本発明の樹脂組成物は銅張積層板、プリント配線板、フレキシブルプリント配線板の基材フィルム、カバーレイフィルム、半導体封止材等の用途に有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024777000001
    Figure 2025024777000001
  • Figure 2025024777000002
    Figure 2025024777000002
  • Figure 2025024777000003
    Figure 2025024777000003
Patent Text Reader

Abstract

To provide a resin composition with a low relative dielectric constant and low dielectric loss tangent, yet yielding a cured product with high adhesion to low-roughness copper, high chemical resistance, and high durability.SOLUTION: A resin composition contains (A) a cyclic imide compound of formula (1), (B) a cyclic imide compound of formula (3), (C) an epoxy compound and (D) a curing catalyst.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a prepreg, a copper-clad laminate, and a printed wiring board. [Background technology]

[0002] In recent years, the speed and capacity of signals used in electronic devices, such as mobile communication devices typified by mobile phones, their base station equipment, network infrastructure devices such as servers and routers, and large computers, are increasing year by year. Accordingly, high frequency bands such as the 20 GHz range are used for the printed wiring boards mounted on these electronic devices, and the properties required of printed wiring board materials are becoming increasingly high, such as low dielectric constant, low dielectric loss tangent, low coefficient of thermal expansion, high heat resistance, and low water absorption.

[0003] Materials that may satisfy these characteristics include epoxy resins, modified polyphenylene ether resins, aromatic maleimide resins, and aliphatic maleimide resins (Patent Documents 1 to 3). However, epoxy resins do not have sufficiently low relative dielectric constants and dielectric loss tangents, and modified polyphenylene ether resins and maleimide resins do not have sufficient adhesive strength to low-roughened copper, so they do not fully satisfy the characteristics required as materials for copper-clad laminates and printed wiring boards. Furthermore, as the frequency band used increases, lower relative dielectric constants, lower dielectric loss tangents, and high adhesiveness to low-roughened copper are required. In addition, aliphatic maleimide resins have a low relative dielectric constant and a low dielectric loss tangent, and have high adhesive strength even to low-roughened copper (Patent Document 4). However, resin compositions containing aliphatic maleimide resins have a drawback in that the chemical resistance is reduced due to the long-chain alkyl group of the aliphatic maleimide, and they are prone to peeling from copper when treated with a desmear solution such as a permanganate solution after via holes are formed by drilling or laser processing in the process of manufacturing printed wiring boards. Compositions containing aliphatic maleimide resins with short alkyl chains have been disclosed, but their desmear treatment resistance and adhesiveness to low-roughened copper have not been studied (Patent Document 5). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-1965 A [Patent Document 2] JP 2018-28044 A [Patent Document 3] JP 2020-176190 A [Patent Document 4] JP 2020-12026 A [Patent Document 5] JP 2021-181531 A Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, an object of the present invention is to provide a resin composition that has a low dielectric constant and a low dielectric tangent, yet gives a cured product that has high adhesion to low-roughened copper, high chemical resistance, and high durability. [Means for solving the problem]

[0006] Means of the Invention The present inventors have conducted extensive research to solve the above problems and have found that the following resin composition can achieve the above object, thereby completing the present invention. That is, the present invention provides the following resin composition, etc.

[0007] [1] A resin composition comprising the following components (A), (B), (C) and (D): A resin composition comprising 60 to 90 parts by mass of component (A) and 10 to 40 parts by mass of component (B) relative to 100 parts by mass in total of components (A) and (B). (A) A cyclic imide compound represented by the following formula (1): [ka] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure, and Q independently represents an alicyclic hydrocarbon group represented by the following formula (2): [ka] (In formula (2), R 1 , R 2 , R 3 , R 4 are independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and x1 and x2 are each an integer of 0 to 4. B is independently any divalent hydrocarbon group represented by the following formula: [ka] (The bond to which no substituent is bonded in the formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (1), and R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; p 1 and p 2 are each a number equal to or greater than 5 and may be the same or different, and p 3 and p 4 are each a number equal to or greater than 0 and may be the same or different, and p 5 and p 6 are numbers equal to or greater than 0 and may be the same or different.) X is a hydrogen atom or a methyl group, n is 1 to 200, m is 0 to 200, and when m is 1 or more, n:m=1:1 to 4:1. The order of each repeating unit bracketed by n and m is not limited. (B) A cyclic imide compound represented by the following formula (3): [ka] In formula (3), A independently represents a tetravalent organic group containing a cyclic structure, and B independently represents any one of the divalent hydrocarbon groups represented by the following formulas: [ka] (The bond to which no substituent is bonded in the formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (1), and R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; p 1 and p 2 are each a number equal to or greater than 5 and may be the same or different, and p 3 and p 4 are each a number equal to or greater than 0 and may be the same or different, and p 5 and p 6 are numbers equal to or greater than 0 and may be the same or different.) X is a hydrogen atom or a methyl group, and s is 0 to 200. (C) Epoxy compounds (D) Curing catalyst [2] The resin composition according to [1], wherein the organic group represented by A in the formula (1) is any one of tetravalent organic groups represented by the following structural formulas: [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).) [3] A prepreg comprising the resin composition according to [1] or [2]. [4] [3] A copper-clad laminate having the prepreg according to the present invention. [5] A printed wiring board having the copper-clad laminate according to [4]. Effect of the Invention

[0008] The resin composition of the present invention is a resin composition having a low relative dielectric constant, a low dielectric loss tangent, high adhesion to low-roughened copper (high peel strength), high chemical resistance (high desmear treatment resistance), and high durability. Therefore, the resin composition of the present invention is useful for applications such as copper-clad laminates, printed wiring boards, and base films for flexible printed wiring boards, coverlay films, and semiconductor encapsulants. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The resin composition of the present invention will be described in detail below.

[0010] [(A) Cyclic imide compound represented by the following formula (1)] The cyclic imide compound of component (A) is an essential component of the resin composition of the present invention and is represented by the following formula (1): By including component (A) in the resin composition of the present invention, the cured product of the resin composition has a low relative dielectric constant, a low dielectric loss tangent, and high chemical resistance. [ka] In formula (1), A independently represents a tetravalent organic group containing a cyclic structure, and Q independently represents an alicyclic hydrocarbon group represented by the following formula (2): [ka] (In formula (2), R 1 , R 2 , R 3 , R 4 are independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and x1 and x2 are each an integer of 0 to 4. B is independently any divalent hydrocarbon group represented by the following formula: [ka] (The bond to which no substituent is bonded in the formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (1), and R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; p 1and p 2 are each a number equal to or greater than 5 and may be the same or different, and p 3 and p 4 are each a number equal to or greater than 0 and may be the same or different, and p 5 and p 6 are numbers equal to or greater than 0 and may be the same or different.) X is a hydrogen atom or a methyl group, n is 1 to 200, m is 0 to 200, and when m is 1 or more, n:m=1:1 to 4:1. The order of each repeating unit bracketed by n and m is not limited.

[0011] Here, the organic groups represented by A in formula (1) are independently tetravalent organic groups containing a cyclic structure, and are particularly preferably any of the tetravalent organic groups represented by the following structural formulas. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).)

[0012] In formula (1), Q is independently an alicyclic hydrocarbon group represented by formula (2) above. In formula (2), R 1 , R 2 , R 3 , R 4 are independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom or a methyl group. In formula (2), x1 and x2 each is an integer of 0 to 4, and preferably an integer of 0 to 2. Incidentally, x1 and x2 may be the same or different. Specific examples of formula (2) include the following structures. [ka]

[0013] In formula (1), B is independently any of the divalent hydrocarbon groups represented by the following formulae: [ka]

[0014] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom forming a cyclic imide structure in formula (1). In the above structural formula, R 1 R each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. 1 is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or a linear alkyl group having 1 to 10 carbon atoms. In the above structural formula, p 1 and p 2 are each a number of 5 or more, preferably a number of 5 to 12, more preferably a number of 6 to 10, and may be the same or different. In the above structural formula, p 3 and p 4 are each a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 3, and may be the same or different. In the above structural formula, p 5 and p 6 are each a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 2, and may be the same or different.

[0015] The divalent hydrocarbon group derived from the dimer acid skeleton is a group derived from dimer acid, a liquid fatty acid mainly composed of a dicarboxylic acid having 36 carbon atoms, which is produced by dimerization of unsaturated fatty acids having 18 carbon atoms, which are derived from natural products such as vegetable oils and fats. Dimer acids do not have a single skeleton, but have multiple structures, and there are several types of isomers. The dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxyl group of such a dimer acid is substituted with a primary aminomethyl group. From the viewpoint of the heat resistance and reliability of the cured product, it is more preferable that the divalent hydrocarbon group derived from the dimer acid skeleton has a structure in which the carbon-carbon double bond in the hydrocarbon group derived from the dimer acid skeleton is reduced by a hydrogenation reaction. Generally, dimer acids may contain trimers (trimer acids) due to the use of natural products such as vegetable oils and fats as raw materials. However, it is preferable that the proportion of hydrocarbon groups derived from dimer acids among the hydrocarbon groups derived from dimer acids and trimer acids is high, for example, 95 mass% or more, because this tends to result in excellent dielectric properties, excellent moldability due to a tendency for the viscosity to decrease when heated, and reduced effects of moisture absorption. As described above, the dimer acid skeleton has a plurality of structures, and therefore, in this specification, the divalent hydrocarbon group derived from the dimer acid skeleton is referred to as the average structure, i.e., -C 36 H 70 It may be written as -.

[0016] In the above formula (1), X is a hydrogen atom or a methyl group, and is preferably a hydrogen atom. In the above formula (1), n ​​is 1-200, preferably 2-100, and more preferably 2-50. In the above formula (1), m is an integer of 0 to 200, preferably 1 to 50, and more preferably 1 to 20. When m is 1 or more, the ratio of n to m is 1:1 to 4:1, preferably 1:1 to 3:1, and more preferably 1:1 to 2:1. This range is preferable because the cured product of the resin composition of the present invention has high chemical resistance. In addition, the order of each repeating unit bracketed by n and m is not limited.

[0017] The weight average molecular weight (Mw) of the cyclic imide compound of component (A) is not particularly limited, but is preferably 500 to 1,000,000, more preferably 1,000 to 100,000, and even more preferably 3,000 to 50,000. If the weight average molecular weight (Mw) is within this range, the resin composition has sufficient strength and the terminal cyclic imide groups can be efficiently reacted.

[0018] The weight average molecular weight (Mw) referred to in this specification refers to the weight average molecular weight measured by GPC under the following conditions using polystyrene as the standard substance (the same applies hereinafter). [GPC measurement conditions] Developing solvent: Tetrahydrofuran Flow rate: 0.6mL / min Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (sample concentration: 0.5% by mass in tetrahydrofuran solution) Detector: Differential refractometer (RI)

[0019] The method for producing the cyclic imide compound (A) (e.g., a maleimide compound, a citraconic imide compound, etc.) is not particularly limited. For example, the compound may be produced by reacting an amine compound with an excess of maleic anhydride or citraconic anhydride, or the compound may be produced by reacting an acid anhydride with a diamine to synthesize an amine-terminated compound, and then reacting the amine-terminated compound with an excess of maleic anhydride or citraconic anhydride.

[0020] Examples of the acid anhydride include pyromellitic anhydride, maleic anhydride, succinic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-diphthalic anhydride, 4,4'-sulfonyldiphthalic anhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, etc. These acid anhydrides may be used alone or in combination of two or more depending on the purpose, application, etc. From the viewpoint of the electrical properties of the cyclic imide compound, the acid anhydride is preferably pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, or 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride.

[0021] Examples of diamines include 1,3-di(aminomethyl)cyclohexane, 1-amino-4-(aminomethyl)cyclohexane, and isophoronediamine as components constituting Q in formula (1), and tetramethyl-1,3-bis(3-aminopropyl)disiloxane, 1,12-diaminododecane, 1,10-diaminodecane, dimer diamine, octyldiamine, 1,3-di(aminomethyl)cyclohexane, isophoronediamine, 2,4,4-trimethylhexane-1,6-diamine, 2-methylpentane-1,5-diamine, and 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0(2,6)]decane, etc. Depending on the purpose, application, etc., one type of these diamines may be used alone, or two or more types may be used in combination. From the viewpoint of the electrical properties of the cyclic imide compound, the diamine is preferably 1,3-di(aminomethyl)cyclohexane or isophoronediamine as the component constituting Q in formula (1), and tetramethyl-1,3-bis(3-aminopropyl)disiloxane, 1,12-diaminododecane, 1,3-diaminoadamantane, 1,10-diaminodecane, dimer diamine, octyldiamine, 2,4,4-trimethylhexane-1,6-diamine or 2-methylpentane-1,5-diamine as the component constituting B in formula (1). It is particularly preferable that the diamine be isophoronediamine as the component constituting Q in formula (1), and that the dimer diamine be used as the component constituting B in formula (1).

[0022] The equivalent weight of the cyclic imide group in the component (A) is preferably 0.001 to 0.5 mol / 100 g, more preferably 0.003 to 0.4 mol / 100 g, even more preferably 0.01 to 0.3 mol / 100 g, and even more preferably 0.02 to 0.2 mol / 100 g. This range is preferable because the cured product of the resin composition has a low relative dielectric constant, a low dielectric tangent, and high adhesion.

[0023] The blending amount of the (A) component is 60 to 90 parts by mass, preferably 65 to 85 parts by mass, and more preferably 70 to 80 parts by mass, based on 100 parts by mass of the total of the (A) component and the (B) component described below. If the blending amount of the (A) component is less than 60 parts by mass, the resin composition containing the (A) component has low chemical resistance, and may peel off from copper when treated with a desmear solution. If the blending amount of the (A) component is more than 90 parts by mass, the resin composition containing the (A) component has low adhesion to copper, and may peel off when forming a via hole with a laser or drill. The cyclic imide compound of the component (A) may be used alone or in combination of two or more kinds.

[0024] [(B) Cyclic imide compound represented by the following formula (3)] The cyclic imide compound of component (B) is an essential component of the resin composition of the present invention and is represented by the following formula (3): By including component (B) in the resin composition of the present invention, the cured product of the resin composition has a low relative dielectric constant, a low dielectric tangent, and high adhesion. [ka] In formula (3), A independently represents a tetravalent organic group containing a cyclic structure, and B independently represents any one of the divalent hydrocarbon groups represented by the following formulas: [ka] (The bond to which no substituent is bonded in the formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (1), and R 1each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; p 1 and p 2 are each a number equal to or greater than 5 and may be the same or different, and p 3 and p 4 are each a number equal to or greater than 0 and may be the same or different, and p 5 and p 6 are numbers equal to or greater than 0 and may be the same or different.) X is a hydrogen atom or a methyl group, and s is 0 to 200.

[0025] Here, the organic groups represented by A in formula (3) are independently tetravalent organic groups containing a cyclic structure, and are particularly preferably any of the tetravalent organic groups represented by the following structural formulas. [ka] (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (3).)

[0026] In formula (3), B is independently any of the divalent hydrocarbon groups represented by the following formulae: [ka]

[0027] The bond not bonded to a substituent in the above structural formula is bonded to the nitrogen atom that forms a cyclic imide structure in formula (3). In the above structural formula, R 1 R each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. 1 is preferably a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms, and more preferably a hydrogen atom or a linear alkyl group having 1 to 10 carbon atoms. In the above structural formula, p 1 and p 2are each a number of 5 or more, preferably a number of 5 to 12, more preferably a number of 6 to 10, and may be the same or different. In the above structural formula, p 3 and p 4 are each a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 3, and may be the same or different. In the above structural formula, p 5 and p 6 are each a number of 0 or more, preferably a number of 0 to 4, more preferably a number of 0 to 2, and may be the same or different.

[0028] In the above formula (3), X is a hydrogen atom or a methyl group, and is preferably a hydrogen atom. In the above formula (3), s is an integer of 0 to 200, preferably 0 to 100, and more preferably 0 to 50.

[0029] The weight average molecular weight (Mw) of the cyclic imide compound of component (B) is not particularly limited, but is preferably 500 to 1,000,000, more preferably 1,000 to 100,000, and even more preferably 3,000 to 50,000. If the weight average molecular weight (Mw) is within this range, the resin composition has sufficient strength and the terminal cyclic imide groups can be efficiently reacted.

[0030] The method for producing the cyclic imide compound of component (B) is not particularly limited. For example, the compound may be produced by reacting an amine compound with an excess of maleic anhydride or citraconic anhydride, or the compound may be produced by reacting an acid anhydride with a diamine to synthesize an amine-terminated compound, and then reacting the amine-terminated compound with an excess of maleic anhydride or citraconic anhydride.

[0031] Examples of the acid anhydride include pyromellitic anhydride, maleic anhydride, succinic anhydride, 4,4'-carbonyldiphthalic anhydride, 4,4'-diphthalic anhydride, 4,4'-sulfonyldiphthalic anhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride, etc. These acid anhydrides may be used alone or in combination of two or more depending on the purpose, application, etc. From the viewpoint of the electrical properties of the cyclic imide compound, the acid anhydride is preferably pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, or 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride.

[0032] Examples of diamines include tetramethyl-1,3-bis(3-aminopropyl)disiloxane, 1,12-diaminododecane, 1,10-diaminodecane, dimer diamine, octyldiamine, 2,4,4-trimethylhexane-1,6-diamine, 2-methylpentane-1,5-diamine, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0(2,6)]decane, etc. Depending on the purpose, application, etc., one type of these diamines may be used alone, or two or more types may be used in combination. From the viewpoint of the electrical properties of the cyclic imide compound, the diamine is preferably an aliphatic diamine such as tetramethyl-1,3-bis(3-aminopropyl)disiloxane, 1,12-diaminododecane, 1,10-diaminodecane, dimer diamine, octyldiamine, 1,3-di(aminomethyl)cyclohexane, 1,3-diaminoadamantane, 2,4,4-trimethylhexane-1,6-diamine, or 2-methylpentane-1,5-diamine, and more preferably dimer diamine or isophoronediamine.

[0033] The cyclic imide compound of component (B) may be a commercially available product, such as BMI-689, BMI-1500, or BMI-3000 (manufactured by Designer Molecules Inc.).

[0034] The equivalent weight of the cyclic imide group in the component (B) is preferably 0.001 to 0.5 mol / 100 g, more preferably 0.003 to 0.4 mol / 100 g, even more preferably 0.01 to 0.3 mol / 100 g, and even more preferably 0.02 to 0.2 mol / 100 g. This range is preferable because the cured product of the resin composition has a low relative dielectric constant, a low dielectric tangent, and high adhesion.

[0035] The blending amount of the (B) component is 10 to 40 parts by mass, preferably 15 to 35 parts by mass, and more preferably 20 to 30 parts by mass, and the total amount with the above-mentioned (A) component is 100 parts by mass. If the blending amount of the (B) component is less than 10 parts by mass, the resin composition containing the (B) component has low adhesion to copper, and peeling may occur when forming a via hole with a laser or a drill. If the blending amount of the (B) component is more than 40 parts by mass, the resin composition containing the (B) component has low chemical resistance, and peeling may occur when treated with a desmear solution. The cyclic imide compound of the component (B) may be used alone or in combination of two or more kinds.

[0036] The total content of components (A) and (B) in the resin composition of the present invention is preferably 60 to 99 mass %, more preferably 65 to 95 mass %, and even more preferably 70 to 95 mass %.

[0037] [(C) Epoxy compound] The epoxy compound (C) is copolymerized with the cyclic imide compounds (A) and (B) and is an essential component of the resin composition of the present invention. The copolymerization of the epoxy group with the cyclic imide group accelerates the curing of the cyclic imide group, thereby improving the adhesiveness.

[0038] The epoxy compound of component (C) is not particularly limited, but examples thereof include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, 3,3',5,5'-tetramethyl-4,4'-biphenol type epoxy compounds, liquid polyfunctional epoxy compounds such as 4,4'-methylenebis(N,N-diglycidianiline) and 4-glycidyloxy(N,N-diglycidianiline), biphenol type epoxy compounds such as 4,4'-biphenol type epoxy compounds, biphenol novolac type epoxy compounds, biphenyl aralkyl type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, bisphenol A novolac type epoxy compounds, naphthalene diol type epoxy compounds, trisphenylol methane type epoxy compounds, tetrakisphenylol ethane type epoxy compounds, phenol dicyclopentadiene novolac type epoxy compounds, and epoxy compounds in which the aromatic ring of a phenol dicyclopentadiene novolac type epoxy compound is hydrogenated. Among these, liquid multifunctional epoxy compounds, biphenol novolac epoxy compounds, phenol novolac epoxy compounds, cresol novolac epoxy compounds, bisphenol A novolac epoxy compounds, biphenyl aralkyl epoxy compounds, and phenol dicyclopentadiene novolac epoxy compounds are preferred. One type of epoxy compound may be used alone, or two or more types may be used in combination. If necessary, a certain amount of epoxy compounds other than the above may be used in combination depending on the purpose.

[0039] The amount of component (C) is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 1 to 7 parts by mass, per 100 parts by mass of the total of components (A) and (B). Within this range, the resin composition can be sufficiently cured without adversely affecting the physical properties of the resin composition.

[0040] [(D) Curing catalyst] The curing catalyst of component (D) is an essential component of the resin composition of the present invention. The curing catalyst of component (D) is not particularly limited, but examples thereof include thermal radical polymerization initiators and thermal anionic polymerization initiators.

[0041] Examples of the thermal radical polymerization initiator include methyl ethyl ketone peroxide, methylcyclohexanone peroxide, methylacetoacetate peroxide, acetylacetone peroxide, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, 2,2-bis(4,4-di-t -butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)cyclododecane, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,2-bis(t-butylperoxy)butane, 1,1-bis(t-butylperoxy)-2-methylcyclohexane, t-butyl hydroperoxide, p-menthane hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-hexyl hydroperoxide, dicumyl peroxide, 2,5-dimethyl 2,5-diethyl-2,5-bis(t-butylperoxy)hexane, α,α'-bis(t-butylperoxy)diisopropylbenzene, t-butylcumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, isobutyryl peroxide, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, cinnamic acid peroxide, m-toluoyl peroxide, benzoyl peroxide, diisopropyl Pyl peroxydicarbonate, bis(4-t-butylcyclohexyl) peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, 1,1,3,3-Tetramethylbutylperoxyneodecanoate, 1-cyclohexyl-1-methylethylperoxyneodecanoate, t-hexylperoxyneodecanoate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexylperoxy peroxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxymaleic acid, t-butylperoxylaurate, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-bis(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxyethylhexanoate, Organic peroxides such as 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide), 2,2'-azobis[N-(2-methylpropyl)-2-methylpropionamide], 2,2'-azobis[N-(2-methylethyl)-2- ... 2,2'-azobis(N-hexyl-2-methylpropionamide), 2,2'-azobis(N-propyl-2-methylpropionamide), 2,2'-azobis(N-ethyl-2-methylpropionamide), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,Examples of the azo compounds include 2'-azobis[N-(2-propenyl)-2-methylpropionamide] and dimethyl-1,1'-azobis(1-cyclohexanecarboxylate).

[0042] Examples of the thermal anionic polymerization initiator include amine compounds such as triethylamine, triethylenediamine, 2-(dimethylaminomethyl)phenol, 1,8-diaza-bicyclo[5.4.0]undecene-7, tris(dimethylaminomethyl)phenol, and benzyldimethylamine; and isomers such as 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2,4-diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine, and 2-phenyl-4-hydroxy-5-methylimidazole. Midazole compounds; and organic phosphorus compounds such as triphenylphosphine, tributylphosphine, trioctylphosphine, tetrabutylphosphonium hexafluorophosphate, tetrabutylphosphonium tetraphenylborate, tetrabutylphosphonium acetate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium bromide, tetrabutylphosphonium bromide, tetrabutylphosphonium laurate, tetraphenylphosphonium hydrogen phthalate, bis(tetraphenylphosphonium) dihydrogen pyromellitate, and bis(tetrabutylphosphonium) dihydrogen pyromellitate.

[0043] Among these, thermal anionic polymerization initiators are preferred, and among these, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2,4-diamino-6-[2-(2-methyl-1-imidazolyl)ethyl]-1,3,5-triazine, and 2-phenyl-4-hydroxy-5-methylimidazole are particularly preferred. These polymerization initiators may be used alone or in combination of two or more.

[0044] The amount of component (D) is not particularly limited, but is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, and even more preferably 0.3 to 3 parts by mass, per 100 parts by mass of the total of components (A) and (B). Within this range, the resin composition can be sufficiently cured without adversely affecting the physical properties of the resin composition.

[0045] [Inorganic filler] The resin composition of the present invention may further contain an inorganic filler (component (E)). The inorganic filler is not particularly limited, and examples thereof include metal oxides such as silica, titanium dioxide, yttrium oxide, aluminum oxide, magnesium oxide, zinc oxide, and beryllium oxide; metal nitrides such as boron nitride, aluminum nitride, and silicon nitride; carbon-containing particles such as silicon carbide, diamond, and graphene; hollow particles such as silica balloons (hollow silica), carbon balloons, alumina balloons, and aluminosilicate balloons; simple metals such as gold, silver, copper, palladium, aluminum, nickel, iron, cobalt, titanium, manganese, zinc, tungsten, platinum, lead, and tin; and alloys such as solder, steel, and stainless steel. ferrites such as stainless steel, Fe-Cr-Al-Si alloy, Fe-Si-Al alloy, Fe-Ni alloy, Fe-Cu-Si alloy, Fe-Si alloy, Fe-Si-B(-Cu-Nb) alloy, Fe-Si-Cr-Ni alloy, Fe-Si-Cr alloy, Fe-Si-Al-Ni-Cr alloy, etc.; hematite (Fe2O3), magnetite (Fe3O4), Mn-Zn ferrite, Ni-Zn ferrite, Mg-Mn ferrite, Zr-Mn ferrite, Ti-Mn ferrite, Mn-Zn-Cu ferrite, barium ferrite, strontium ferrite, etc. These may be used alone or in combination of two or more.

[0046] By adding metal oxides, metal nitrides, and carbon-containing particles, the linear expansion coefficient of the cured resin composition can be reduced and the thermal conductivity can be increased; by adding hollow particles, the relative dielectric constant, dielectric tangent, density, etc. of the cured resin composition can be reduced; by adding metals and alloys, the electrical conductivity, thermal conductivity, etc. of the cured resin composition can be increased; and by adding ferrites, the cured resin composition can be endowed with electromagnetic wave absorption ability.

[0047] The shape of the inorganic filler is not particularly limited, and examples thereof include spherical, scaly, flake-like, needle-like, rod-like, and elliptical shapes. Among these, spherical, scaly, flake-like, elliptical, and rod-like shapes are preferred, and spherical, scaly, flake-like, and elliptical shapes are more preferred.

[0048] The primary particle size of the inorganic filler is not particularly limited, but is preferably 0.05 to 500 μm, more preferably 0.1 to 300 μm, and even more preferably 1 to 100 μm, as a median diameter measured by a laser diffraction particle size distribution measuring device. If it is within this range, it is easy to uniformly disperse the inorganic filler in the resin composition, and the inorganic filler does not settle, separate, or become unevenly distributed over time, which is preferable.

[0049] The amount of the inorganic filler is not particularly limited, but is preferably 5 to 3,000 parts by mass, more preferably 10 to 2,500 parts by mass, and even more preferably 50 to 2,000 parts by mass, relative to 100 parts by mass of the total of components (A) and (B) in the composition of the present invention. Within this range, the function of the inorganic filler can be fully exerted while maintaining the strength of the resin composition.

[0050] [Organic filler] The resin composition of the present invention may further contain an organic filler (component (F)). The organic filler is not particularly limited, and examples thereof include thermoplastic resin particles such as acrylic-butadiene copolymer, styrene-butadiene copolymer, acrylonitrile-styrene-butadiene copolymer, acrylic block copolymer, carbon fiber, cellulose fiber, silicone powder, acrylic powder, polytetrafluoroethylene powder, polyethylene powder, polypropylene powder, etc. These may be used alone or in combination of two or more.

[0051] The shape of the organic filler is not particularly limited, and examples thereof include spherical, fibrous, flake-like, needle-like, rod-like, and elliptical shapes. Among these, spherical, fibrous, flake-like, elliptical, and rod-like shapes are preferred, and spherical, fibrous, flake-like, and elliptical shapes are more preferred.

[0052] The primary particle size of the organic filler is not particularly limited, but is preferably 0.05 to 500 μm, more preferably 0.1 to 300 μm, and even more preferably 1 to 100 μm, as a median diameter measured by a laser diffraction particle size distribution measuring device. If it is within this range, it is preferable because it is easy to uniformly disperse the organic particles in the resin composition and the organic particles do not settle, separate, or become unevenly distributed over time.

[0053] The amount of the organic filler is not particularly limited, but is preferably 1 to 400 parts by mass, more preferably 5 to 200 parts by mass, and even more preferably 10 to 100 parts by mass, per 100 parts by mass of the total of the (A) and (B) components in the composition of the present invention. If the amount is within this range, it is possible to increase the strength of the resin composition.

[0054] [Adhesion promoter] The resin composition of the present invention may contain an adhesion imparting agent (component (G)) as necessary to impart adhesiveness or tackiness (pressure-sensitive adhesiveness). Examples of adhesion imparting agents include acrylic resins, urethane resins, phenolic resins, terpene resins, and silane coupling agents. Among these, acrylic resins and silane coupling agents are preferred for imparting adhesiveness, and terpene resins are preferred for imparting tackiness (pressure-sensitive adhesiveness). The adhesion imparting agent of component (G) may be used alone or in combination of two or more types.

[0055] The acrylic resin is not particularly limited, and examples thereof include lauryl acrylate, stearyl acrylate, isostearyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, tetrahydrofurfuryl acrylate, isobornyl acrylate, 2-acryloyloxyethyl phthalate, 2-acryloyloxyethyl acid phosphate, polyethylene glycol diacrylate, dimethylol tricyclodecane diacrylate, trimethylolpropane triacrylate, dipentaerythritol hexaacrylate, and the like. Examples of suitable methacrylates include tetrahydrofurfuryl methacrylate, dioxane glycol diacrylate, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate, lauryl methacrylate, phenoxyethyl methacrylate, phenoxydiethylene glycol methacrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, 2-methacryloyloxyethyl phthalate, 2-methacryloyloxyethyl acid phosphate, polyethylene glycol dimethacrylate, and dimethylol tricyclodecane dimethacrylate.

[0056] The terpene resin is not particularly limited, and examples thereof include homopolymers of terpenes such as monoterpenes such as α-pinene, β-pinene, dipentene, and limonene, sesquiterpenes such as cedrene and farnesene, and diterpenes such as abietic acid, aromatic modified terpene resins which are copolymers of aromatic vinyl compounds such as styrene and α-methylstyrene with the above-mentioned terpenes, and terpene phenol resins which are copolymers of phenols such as phenol, cresol, hydroquinone, naphthol, and bisphenol A with the above-mentioned terpenes, etc. In addition, hydrogenated terpene resins obtained by hydrogenating these terpene resins can also be used.

[0057] The silane coupling agent is not particularly limited, and examples thereof include silane coupling agents such as n-propyltrimethoxysilane, n-propyltriethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, 2-[methoxy(polyethyleneoxy)propyl]-trimethoxysilane, methoxytri(ethyleneoxy)propyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and 3-isocyanatopropyltrimethoxysilane.

[0058] The amount of the adhesion promoter is not particularly limited, but is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 1 to 5 parts by mass, per 100 parts by mass of the total of components (A) and (B). Within this range, the adhesive strength or cohesive strength of the resin composition can be further improved without changing the mechanical properties of the resin composition.

[0059] [Antioxidants] The resin composition of the present invention may contain an antioxidant (component (H)) as necessary.The antioxidant is not particularly limited, and examples thereof include n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, n-octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)acetate, neododecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, dodecyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, ethyl Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butylphenyl)isobutyrate, Octadecyl-α-(4-hydroxy-3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(n-octylthio)ethyl-3,5-di-t-butyl-4-hydroxyphenylacetate, 2-(n-octadecylthio)ethyl-3, 5-di-t-butyl-4-hydroxyphenyl acetate, 2-(n-octadecylthio)ethyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2-(2-stearoyloxyethylthio)ethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)heptanoate, 2-hydroxyethyl-7-(3-methyl-5-t-butyl-4-hydroxyphenyl)propionate, pentaethyl Phenolic antioxidants such as rhythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]; sulfur-based antioxidants such as dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, and pentaerythrityl tetrakis (3-laurylthiopropionate);Examples of phosphorus-based antioxidants include tridecyl phosphite, triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, 2-ethylhexyl diphenyl phosphite, diphenyl tridecyl phosphite, 2,2-methylene bis(4,6-di-t-butylphenyl)octyl phosphite, distearyl pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite, and 2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-N,N-bis[2-[[2,4,8,10-tetrakis(1,1-dimethylethyl)dibenzo[d,f][1,3,2]dioxaphosphepin-6-yl]oxy]-ethyl]ethanamine. The antioxidant of component (H) may be used alone or in combination of two or more kinds.

[0060] The amount of the antioxidant is not particularly limited, but is preferably 0.00001 to 5 parts by mass, more preferably 0.0001 to 4 parts by mass, and even more preferably 0.001 to 3 parts by mass, per 100 parts by mass of the total of components (A) and (B). If it is within this range, oxidation of the resin composition can be prevented without changing the mechanical properties of the resin composition.

[0061] [Flame retardant] The resin composition of the present invention may contain a flame retardant (component (I)) as necessary in order to impart flame retardancy. The flame retardant is not particularly limited, and examples thereof include phosphorus-based flame retardants, metal hydrates, halogen-based flame retardants, guanidine-based flame retardants, etc. Examples of phosphorus-based flame retardants include red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, inorganic nitrogen-containing phosphorus compounds such as guanidine phosphate and phosphoric acid amide, phosphoric acid, phosphine oxide, triphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, cresyl diphenyl phosphate, cresyl di-2,6-xylenyl phosphate, resorcinol bis(diphenyl phosphate), 1,3-phenylene bis(di-2,6-xylenyl phosphate), bisphenol A-bis(diphenyl phosphate), 1,3-phenylene bis( Examples of suitable phosphazene compounds include phosphazene compounds such as diphenyl phosphate, divinyl phenylphosphonate, diallyl phenylphosphonate, bis(1-butenyl) phenylphosphonate, phenyl diphenylphosphinate, methyl diphenylphosphinate, bis(2-allylphenoxy)phosphazene, and dicresylphosphazene, as well as melamine phosphate, melamine pyrophosphate, melamine polyphosphate, melam polyphosphate, melem polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Examples of suitable metal hydrates include aluminum hydroxide hydrate and magnesium hydroxide hydrate. Examples of halogen-based flame retardants include hexabromobenzene, pentabromotoluene, ethylene bis(pentabromophenyl), ethylene bistetrabromophthalimide, 1,2-dibromo-4-(1,2-dibromoethyl)cyclohexane, tetrabromocyclooctane, hexabromocyclododecane, bis(tribromophenoxy)ethane, brominated polyphenylene ether, brominated polystyrene, 2,4,6-tris(tribromophenoxy)-1,3,5-triazine, etc. Examples of guanidine-based flame retardants include guanidine sulfamate, guanidine phosphate, etc. The flame retardants of the component (I) may be used alone or in combination of two or more.

[0062] The amount of the flame retardant is not particularly limited, but is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 4 parts by mass, and even more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the total of the (A) and (B) components. Within this range, flame retardancy can be imparted to the resin composition without changing the mechanical properties of the resin composition.

[0063] [Manufacturing method] The method for producing the resin composition of the present invention includes, for example, a method of mixing the components (A) to (D) and other components added as necessary using a planetary mixer (manufactured by Inoue Seisakusho Co., Ltd.) or a mixer THINKY CONDITIONING MIXER (manufactured by Thinky Corporation), and preferably a method of further adding and mixing an organic solvent (e.g., cyclopentanone, cyclohexanone, mesitylene, anisole, dibutyl ether, diphenyl ether, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, etc.). By adding an organic solvent, the viscosity of the resin composition can be reduced and more uniformly mixed. The organic solvent is distilled off under reduced pressure after mixing to obtain a resin composition, but when used as a prepreg, it may be used as it is without distilling off, or may be adjusted to a desired concentration before use.

[0064] [Prepreg] The resin composition of the present invention can also be used as a prepreg by dissolving it in the above-mentioned organic solvent, impregnating a fiber substrate with the composition, and drying the resulting solution by heating. The fiber substrate may be any known fiber substrate used in laminates. Examples include inorganic fibers such as E glass, S glass, T glass, NE glass, and Q glass (quartz glass); and organic fibers such as polyethylene, polyester, polyamide, and polytetrafluoroethylene. These may be used alone or in combination of two or more. Among these, inorganic fibers are preferred from the viewpoint of dielectric properties, and T glass, NE glass, and Q glass are more preferred. The thickness of the fiber base material is not particularly limited, but is preferably 5 to 500 μm, more preferably 10 to 100 μm, and even more preferably 20 to 80 μm. Within this range, a prepreg with excellent flexibility, low warpage, and high strength can be obtained. These fiber substrates may be surface-treated by heating or with a silane coupling agent or the like in order to improve the dielectric properties and affinity to resins. The content of the resin composition in the prepreg is not particularly limited, but is preferably 20 to 90% by volume, more preferably 30 to 80% by volume, and even more preferably 40 to 70% by volume. Within this range, the adhesive strength to the conductor can be increased while maintaining the dielectric properties and low warpage. The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 500 μm, more preferably 25 to 300 μm, and even more preferably 40 to 200 μm. If it is within this range, a copper-clad laminate can be satisfactorily produced. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the resin composition of the present invention may be dissolved in a solvent, impregnated into a fiber substrate, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-staging.

[0065] [Copper-clad laminate] The prepreg of the present invention may be used as a copper-clad laminate by overlapping copper foil, pressing, and heat curing. There are no particular limitations on the method for producing a copper-clad laminate, but it can be produced, for example, by using 1 to 20 sheets, preferably 2 to 10 sheets, of the prepreg, placing copper foil on one or both sides, pressing, and heat-curing. The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate that maintains high reliability can be formed. The molding conditions for the copper-clad laminate are not particularly limited, but for example, molding can be performed using a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, etc., at a temperature of 100 to 400°C, a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. Also, the prepreg of the present invention, copper foil, and an inner layer wiring board can be combined and molded to form a copper-clad laminate.

[0066] [Printed wiring board] The copper-clad laminate of the present invention may be subjected to circuit processing and used as a printed wiring board. The method of circuit processing is not particularly limited, but examples thereof include circuit formation processing by drilling, metal plating, etching of metal foil, and the like. Furthermore, a printed wiring board may be produced by a build-up method in which the resin composition or prepreg of the present invention and copper foil are laminated in that order. EXAMPLES

[0067] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0068] The molecular weights shown in the following examples are weight average molecular weights (Mw) measured by gel permeation chromatography (GPC) using polystyrene as a standard substance. The measurement conditions are as follows: [GPC measurement conditions] Developing solvent: Tetrahydrofuran Flow rate: 0.6mL / min Column: TSK Guardcolumn SuperH-L TSKgel SuperH4000(6.0mmI.D.×15cm×1) TSKgel SuperH3000(6.0mmI.D.×15cm×1) TSKgel SuperH2000(6.0mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 20 μL (sample concentration: 0.5% by mass in tetrahydrofuran solution) Detector: Differential refractometer (RI)

[0069] (A) Cyclic imide compound (A-1) 114g (1.0mol) of 1,4-cyclohexanediamine and 499g (0.96mol) of 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A-1) represented by the following formula. (Weight average molecular weight 18,000, maleimide equivalent 0.011mol / 100g) [ka]

[0070] (A-2) 113g (0.67mol) of isophoronediamine, 174g (0.33mol) of dimer diamine and 209g (0.96mol) of pyromellitic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A-2) represented by the following formula. (Weight average molecular weight 15,000, maleimide equivalent 0.013mol / 100g) [ka]

[0071] (A-3) 136g (0.80mol) of isophoronediamine, 104g (0.20mol) of dimer diamine and 298g (0.96mol) of 4,4'-diphthalic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A-3) represented by the following formula. (Weight average molecular weight 21,000, maleimide equivalent 0.0095mol / 100g) [ka]

[0072] (A'-1) 100g (0.5mol) of dodecanediamine, 264g (0.5mol) of dimer diamine and 298g (0.96mol) of 4,4'-oxydiphthalic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A'-1) represented by the following formula. (Weight average molecular weight 13,000, maleimide equivalent 0.015mol / 100g) [ka]

[0073] (A'-2) 206g (0.67mol) of 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 174g (0.33mol) of dimer diamine and 298g (0.96mol) of 4,4'-oxydiphthalic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A'-2) represented by the following formula. (Weight average molecular weight 20,000, maleimide equivalent 0.010mol / 100g) [ka]

[0074] (A'-3) 101g (0.33mol) of 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 353g (0.67mol) of dimer diamine and 298g (0.96mol) of 4,4'-oxydiphthalic anhydride were added to 263g of N-methylpyrrolidone, and the mixture was stirred at 25°C for 3 hours, and then further stirred at 150°C for 5 hours. 196g (2.0mol) of maleic anhydride, 82g (1.0mol) of sodium acetate and 204g (2.0mol) of acetic anhydride were added to the obtained solution, and the mixture was stirred at 80°C for 1 hour. Then, 500g of toluene was added, and the mixture was washed with water and dehydrated, and the solvent was distilled off under reduced pressure to obtain bismaleimide (A'-3) represented by the following formula. (Weight average molecular weight 23,000, maleimide equivalent 0.0087mol / 100g) [ka]

[0075] (B) Cyclic imide compound (B-1) Maleimide compound represented by the following formula (BMI-3000, manufactured by Designer Molecules Inc.) (weight average molecular weight 10,000, maleimide equivalent 0.020 mol / 100 g) [ka]

[0076] (B-2) Maleimide compound represented by the following formula (BMI-1500, manufactured by Designer Molecules Inc.) (weight average molecular weight 3,000, maleimide equivalent 0.067 mol / 100 g) [ka]

[0077] (B-3) Maleimide compound represented by the following formula (BMI-689, manufactured by Designer Molecules Inc.) (weight average molecular weight 700, maleimide equivalent 0.29 mol / 100 g) [ka]

[0078] (C) Epoxy compounds (C-1) Biphenyl aralkyl type epoxy resin (product name "NC-3000" (manufactured by Nippon Kayaku Co., Ltd.)) (C-2) Bisphenol A type epoxy resin (product name "jER-828EL" (manufactured by Mitsubishi Chemical Corporation))

[0079] (D) Curing catalyst (D-1) 2-Ethyl-4-methylimidazole

[0080] (E) Inorganic filler (E-1) Silica "SFP-130MC" (median primary particle size: 0.6 μm) (manufactured by Denka Co., Ltd.)

[0081] (F) Organic filler (F-1) Silicone powder "KMP-600" (median primary particle size: 5 μm) (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0082] (G) Adhesion promoter (G-1) Silane coupling agent (3-glycidoxypropyltrimethoxysilane, trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.)

[0083] (H) Antioxidants (H-1) Pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] (product name "ADEKA STAB AO-60", manufactured by ADEKA Corporation)

[0084] (I) Flame retardants (I-1) Guanidine phosphate (product name "Apinon-303", manufactured by Sanwa Chemical Co., Ltd.)

[0085] [Method for preparing resin composition] For Examples 1 to 12 and Comparative Examples 1 to 7, in addition to the formulations (parts by mass) shown in Tables 1 and 2, 100 parts by mass of cyclopentanone was added and mixed for a total of 100 parts by mass of each component, and the mixture was kneaded at 80° C. for 30 minutes using a planetary mixer (Inoue Seisakusho Co., Ltd.), and then cooled to 25° C. The resulting solution was transferred to a flask, and the solvent was distilled off under reduced pressure to prepare a resin composition.

[0086] [Dielectric constant and dielectric loss tangent] The prepared resin composition was sandwiched between a mold frame of 30 mm x 40 mm x 100 μm thickness, and press cured at 180 ° C and 3 MPa for 1 hour to prepare a test sample. A network analyzer (Keysight E5063-2D5) and a strip line (Keycom Co., Ltd.) were connected to the prepared test sample to measure the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz. The results are shown in Tables 1 and 2.

[0087] [Peel Strength] The resin composition prepared by the above method was coated in a film shape to a thickness of 25 μm to prepare a resin film, and a SUS plate, the resin film, and a copper foil having a thickness of 18 μm (product name: TQ-M4-VSP, manufactured by Mitsui Metals Co., Ltd.) were stacked in this order and press-cured at 180 ° C. and 3 MPa for 1 hour to prepare a test sample. In accordance with the standard JIS-C-6481:1996 for testing copper-clad laminates for printed wiring boards, the force (peel strength) when peeling the copper foil from the resin film at a speed of 50 mm / min in a 90° direction with a width of 10 mm was measured using a Tensilon tester (manufactured by Toyo Seiki Seisakusho Co., Ltd., product name: Strograph VE-1D). The results are shown in Tables 1 and 2.

[0088] [Desmear treatment resistance] The prepared resin composition was sandwiched between a mold frame of 30 mm x 40 mm x 100 μm thickness, and press cured at 180°C and 3 MPa for 1 hour to prepare a test sample. The weight loss rate of the prepared test sample before and after the desmear treatment was calculated (mass loss (g) / test piece surface area (dm2)). The desmear treatment was performed in the order of swelling (70°C, 5 minutes), roughening (80°C, 10 minutes), neutralization (40°C, 5 minutes), and water washing (room temperature, 5 minutes). The test liquids used were swelling liquid, desmear liquid, and neutralization liquid manufactured by Atotech, adjusted to the specified concentrations. The results are shown in Tables 1 and 2.

[0089] [Table 1]

[0090] [Table 2]

[0091] In Examples 1 to 12, the cured products had low relative dielectric constants and low dielectric tangents, high peel strength (high adhesion to low-roughened copper), and sufficient resistance to desmear treatment. In Comparative Example 1, the group corresponding to Q in formula (1) of the component (A) was a linear hydrocarbon group, and therefore the resistance to desmear treatment was low. In Comparative Examples 2 and 3, the group corresponding to Q in formula (1) of the component (A) was an aromatic hydrocarbon group, and so the dielectric tangent values ​​were high. In Comparative Examples 4 and 6, the peel strength (adhesion to low-roughened copper) was low because the component (B) was not contained or the amount of the component (B) was small relative to the amount of the component (A). In Comparative Examples 5 and 7, the component (A) was not contained or the amount of the component (A) blended was small relative to the amount of the component (B) blended, and therefore the desmear treatment resistance was low.

[0092] [Prepreg manufacturing method] In Examples 13 to 16 and Comparative Examples 8 to 11, 1,000 g of each of the resin compositions prepared in Examples 1 to 4 and Comparative Examples 4 to 7 was mixed with 1,000 g of cyclopentanone, impregnated into a quartz glass cloth SQX2116AC (thickness 90 μm, manufactured by Shin-Etsu Chemical Co., Ltd.), and heated at 120° C. for 5 minutes to volatilize the cyclopentanone, thereby producing a prepreg. The content (mass%) of the resin composition and the thickness of the prepreg are shown in Table 3.

[0093] [Manufacturing method of copper clad laminate] Ten sheets of the prepregs obtained above and nine sheets of 18 μm thick copper foil (product name: TQ-M4-VSP, manufactured by Mitsui Metals Co., Ltd.) were stacked alternately, and copper foil was further placed on the top and bottom surfaces. The resulting mixture was pressed at 3 MPa and heated at 180°C for 1 hour to produce a double-sided copper-clad laminate.

[0094] [Manufacturing method for printed wiring boards] A 30μm-thick dry resist film (NIT430E, Nikko Materials Co., Ltd.) was vacuum laminated at 80℃ for 60 seconds on both sides of the double-sided copper-clad laminate obtained above. A mask with a circuit pattern was then contacted, and UV was irradiated from above and below at an illuminance of 500mW for 10 seconds. The board was then developed by immersing in a 10% aqueous sodium bicarbonate solution at 40℃ for 10 minutes. The board was then etched by immersing in an etching solution (H-1000A, Sanhayato Co., Ltd.) at 40℃ for 10 minutes. The board was then immersed in a 10% aqueous sodium hydroxide solution at 40℃ for 20 minutes and washed to produce a printed wiring board with circuits formed on both sides.

[0095] [Transmission loss] Using a network analyzer (Keysight Technologies, part number E5071C), the transmission loss at 40 GHz was measured with the conductor length set to 400 mm, the copper foil thickness set to 18 μm, the line width set to 0.12 mm, the insulation layer thickness set to 0.20 mm, and the characteristic impedance set to 50 Ω. The results are shown in Table 3.

[0096] [Temperature cycle test] The produced printed wiring board was subjected to a thermal cycle test (TCT) of 1,000 times at −65° C. to 125° C., and the occurrence of electrical continuity defects was observed. The results are shown in Table 3.

[0097] [Table 3]

[0098] In all of Examples 13 to 16, the transmission loss was low and no conduction failure was observed. In Comparative Examples 8 and 10, the peel strength (adhesion to low-roughening copper) between the resin and the copper foil was low, and therefore poor conductivity occurred in the temperature cycle test. In Comparative Examples 9 and 11, the resin had poor resistance to desmear treatment, and the interface between the resin and the copper foil became rough, resulting in high transmission loss.

Claims

1. A resin composition comprising the following components (A), (B), (C) and (D): A resin composition comprising 60 to 90 parts by mass of component (A) and 10 to 40 parts by mass of component (B) relative to 100 parts by mass in total of component (A) and component (B). (A) A cyclic imide compound represented by the following formula (1): 【Chemistry 1】 In formula (1), A independently represents a tetravalent organic group having a cyclic structure, and Q independently represents an alicyclic hydrocarbon group represented by the following formula (2): 【Chemistry 2】 (In formula (2), R 1 , R 2 , R 3 , R 4 are independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and x1 and x2 each are an integer of 0 to 4. B is independently any divalent hydrocarbon group represented by the following formula: 【Chemistry 3】 (The bond to which no substituent is bonded in the formula is bonded to a nitrogen atom that forms a cyclic imide structure in formula (1), and R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; 1 and p 2 are each a number of 5 or more, and may be the same or different; p 3 and p 4 are each a number of 0 or more and may be the same or different, p 5 and p 6 are each a number equal to or greater than 0, and may be the same or different.) X is a hydrogen atom or a methyl group, n is 1 to 200, m is 0 to 200, and when m is 1 or more, n:m=1:1 to 4:

1. The order of the repeating units bracketed by n and m is not limited. (B) A cyclic imide compound represented by the following formula (3): 【Chemistry 4】 In formula (3), A independently represents a tetravalent organic group containing a cyclic structure, and B independently represents any one of divalent hydrocarbon groups represented by the following formulas: 【Chemistry 5】 (The bond to which no substituent is bonded in the formula is bonded to a nitrogen atom that forms a cyclic imide structure in formula (1), and R 1 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms; 1 and p 2 are each a number of 5 or more, and may be the same or different; p 3 and p 4 are each a number of 0 or more and may be the same or different, p 5 and p 6 are each a number equal to or greater than 0, and may be the same or different.) X is a hydrogen atom or a methyl group, and s is 0 to 200. (C) Epoxy compound (D) Curing catalyst

2. 2. The resin composition according to claim 1, wherein the organic group represented by A in formula (1) is any one of tetravalent organic groups represented by the following structural formulas: 【Chemistry 6】 (The bond not bonded to a substituent in the above structural formula is bonded to the carbonyl carbon that forms a cyclic imide structure in formula (1).)

3. A prepreg comprising the resin composition according to claim 1 or 2.

4. A copper-clad laminate comprising the prepreg according to claim 3.

5. A printed wiring board comprising the copper clad laminate according to claim 4.

Citation Information

Patent Citations

  • Bismaleimide compound and production method thereof

    JP2021123672A

  • Thermosetting maleimide resin composition, adhesive using the same, substrate material, primer, coating material and semiconductor device

    JP2021181531A

  • Heat-curable maleimide resin composition

    JP2022097398A

  • Cyclic imide resin composition, prepreg, copper-clad laminate, and printed wiring board

    JP2022099397A

  • Cyclic imide resin composition, liquid adhesive, film, prepreg, copper-clad laminate, and printed wiring board

    JP2023062903A